Analysis of Factors Influencing Purchase Intention of Local Skincare Products: Mediated by Brand Awareness - Qadri, Rizni Aulia; Waty, Indah; Purwianti, Lily (Profit: Jurnal Adminsitrasi Bisnis, 2026)
Indonesia’s skincare market is expanding quickly, yet ongoing concerns about overstated claims continue to threaten consumer trust and the effectiveness of digital persuasion. Using the Stimulus–Organism–Response (S–O–R) framework, this study examines how influencer credibility, trustworthiness, and attractiveness, along with online customer reviews, influence purchase intention, while positioning brand awareness as a mediator. The research adopted a quantitative, causal-comparative approach with non-probability, judgmental sampling. Data were gathered from 366 residents of Batam City who had purchased, or planned to purchase, local skincare products after encountering influencer content and online reviews between December 2024 and March 2025. Analysis was conducted using SEM-PLS in SmartPLS 4.0. Findings show that all stimulus variables significantly and positively enhance brand awareness, with online customer reviews emerging as the strongest driver of this effect. Brand awareness has a significant positive influence on purchase intention and fully mediates the relationships between each stimulus factor and purchase intention. The results highlight brand awareness as a key cognitive pathway that translates digital marketing inputs into consumer intent to purchase. In practice, local skincare firms should collaborate with credible influencers and strategically cultivate genuine reviews to enhance long-term brand awareness and mitigate skepticism associated with overclaiming.